STRATEGI KOMUNIKASI ORGANISASI FUNGSI HSSE PT PERTAMINA PATRA NIAGA DALAM MENJAGA CITRA PERUSAHAAN - Fitria Putri Mahanani; Maria Febiana Christanti; Uljanatunnisa Uljanatunnisa (Jurnal Pustaka Komunikasi, 2020)
The purpose of this research is to study communication strategy carried out by PT Pertamina Patra Niaga's HSSE (Health, Safety, Security and Environment) Function in overcoming all problems that might occur and affecting the corporate's image. In this study, the study used a qualitative exploratory case study method. This method was chosen because this research only focuses on the HSSE function at PT Pertamina Patra Niaga. The data used is a combination of documents, results of interviews, and observations made by researchers of the HSSE Function of PT Pertamina Patra Niaga. The results of this study discuss the HSSE function of PT Pertamina Patra Niaga is an important function in relation to the company's image. This function is structured based on the interests of companies that will be risky (high risk). In carrying out the main duties and functions of the HSSE, this function carries out various communication strategies in relation to the organization to civilize the safety aspects of all stakeholders in the corporate with objectives related to safety imaging.